Repetitive Peripheral Magnetic Nerve Stimulation (rPMS) as Adjuvant Therapy Reduces Skeletal Muscle Reflex Activity - Zschorlich, Volker R.; Hillebrecht, Martin; Tanjour, Tammam; Qi, Fengxue; Behrendt, Frank; Kirschstein, Timo; Köhling, Rüdiger (Frontiers in Neurology, 2019)
Background: The reduction of muscle hypertonia and spasticity, as well as an increase in mobility, is an essential prerequisite for the amelioration of physiotherapeutical treatments. Repetitive peripheral magnetic nerve stimulation (rPMS) is a putative adjuvant therapy that improves the mobility of patients. Methods: Thirty-eight participants underwent either an rPMS treatment (N=19) with a 5 Hz stimulation protocol at the soleus muscle or with sham stimulation (N=19). The stimulation took place over 5 minutes. The study was conducted in a pre-test post-test design with matched groups. Results: The primary outcome was a significant reduction of the reflex activity of the soleus muscle, triggered by a computer-aided tendon-reflex impact. Outcome measures were taken at the baseline and after the following intervention. The pre-post differences of the tendon reflex response activity were -23.7% (P < 0.001) for the treatment group. No significant effects showed in the sham stimulation group. Conclusion: Low-frequency magnetic stimulation (5 Hz rPMS) exhibits a substantial reduction of the tendon reflex amplitude. The 5 Hz rPMS treatment seems to be an effective procedure to reduce muscular stiffness, increase mobility, and thus, makes the therapeutic effect of neuro-rehabilitation more effective. For this reason, the 5 Hz rPMS treatment might have the potential to be used as an adjuvant therapy in the rehabilitation of gait and posture control in patients suffering from limited mobility due to spasticity.